Arthroscopic rotator cuff repair: suture anchor properties, modes of failure and technical considerations. (May 2011) - Ma, Richard; Chow, Robert; Choi, Luke; Diduch, David
Rotator cuff injury and tears are a common source of shoulder pain, particularly among the elderly. Arthroscopic repair has now become the mainstay in the treatment of significant injuries that have failed conservative therapy. Compared with the traditional open technique, arthroscopic repair offers patients smaller incisions and less soft-tissue trauma, which result in improved postoperative pain and rehabilitation. The advances that have made arthroscopic repairs a reality includes improvement in arthroscopic rotator cuff instrumentation, particularly suture anchors. Suture anchors are used to reattach the torn rotator cuff tissue back onto the bone. Current rotator cuff anchors vary by design, anchor composition and suture materials. A treating physician should be aware of the advantages and limitations of these implants, which may influence the choice of one anchor over another. In addition to anchor variables, other factors that may affect the success of the repair include the local environment and surgical technique. In this article, various aspects of anchor design will be discussed. In addition, a concise review of technical considerations will also be discussed.